PENINGKATAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI PERMAINAN BERBURU ANGKA PADA AUD DI TK NURUL HIDAYAH LEMPANGAN - Mutmainnah Mutmainnah; Wahyuni Ismail; M. Rusdi Tahir; Thamrin Tayeb; Muhammad Ikbal (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2022)
This study aims: 1) to describe the ability to recognize the concept of numbers before the number hunting game is applied to early childhood group A at Kindergarten Nurul Hidayah Lempangan; 2) to describe the ability to recognize the concept of numbers after a number hunting game was applied to early childhood group A at Kindergarten Nurul Hidayah Lempangan; and 3) to find out whether there is a difference in the average ability to recognize number concepts before and after the number hunting game is applied to early childhood group A at Kindergarten Nurul Hidayah Lempangan. This type of research uses quantitative research with experimental type using a census, namely the entire population is subject to research. The population in this study was group A at Kindergarten Nurul Hidayah Lempangan, totaling 6 people. Data collection techniques using observation, tests, and documentation. The data analysis technique used descriptive data analysis with descriptive average (mean).The results of the descriptive test showed: 1) the ability to recognize the concept of numbers before the number hunting game was applied to early childhood group A at Kindergarten Nurul Hidayah Lempangan obtained an average score of 6.67. 2) the ability to recognize the concept of numbers after the number hunting game was applied to early childhood group A at Kindergarten Nurul Hidayah Lempangan obtained an average score of 13.83. 3) there is a difference in the average ability to recognize number concepts in early childhood group A at Kindergarten Nurul Hidayah Lempangan after the number hunting game is applied. The implication of this research is that this research can add insight to children in recognizing the concept of numbers, educators can apply number hunting games in learning activities and can be used as an initial reference source by researchers who are researching the same.